Electronic band structure imaging of three layer twisted graphene on single crystal Cu(111) - Marquez Velasco, J.; Kelaidis, N.; Xenogiannopoulou, E.; Raptis, Y.S.; Tsoutsou, D.; Tsipas, P.; Speliotis, Th.; Pilatos, G.; V. Likodimos; P. Falaras; Dimoulas, A. (Applied Physics Letters, 2013)
Few layer graphene (FLG) is grown on single crystal Cu(111) by Chemical Vapor Deposition, and the electronic valence band structure is imaged by Angle-Resolved Photo-Emission Spectroscopy. It is found that graphene essentially grows polycrystalline. Three nearly ideal Dirac cones are observed along the Cu Γ ̄ K ̄ direction in k-space, attributed to the presence of ∼4°twisted three layer graphene with negligible interlayer coupling. The number of layers and the stacking order are compatible with Raman data analysis demonstrating the complementarity of the two techniques for a more accurate characterization of FLG. © 2013 AIP Publishing LLC.
cited By 8